"Who is going to reform the reformers?" The coordination of the Greek National Reform Programmes - Andreou, George (Ελληνική Επιθεώρηση Πολιτικής Επιστήμης, 2017)
The article studies the impact of the revised Lisbon Strategy -and the National Reform Programmes (NRPs) in particular- on the EU policy coordination of Greece. It is argued that the structures and processes established for the formulation and monitoring of the NRPs reflect some deep-rooted characteristics of the Greek system of governance, namely centralism, politicization, informality and reliance on actors. It is also found that the demise of this policy network was caused not by domestic factors or developments, but by the insistence of Greece’s EU partners to fuse the implementation of the Greek NRP with the execution of the 2010 economic adjustment programme. The introduction of this process of coercive-direct Europeanization in Greece (as well as in Ireland and Portugal) signals, inter alia, the emergence of a two-speed "Europe 2020". On the other hand, the new reform coordination process in Greece relies on preexisting structures and processes that closely follow traditional patterns.